As empresas familiares e os desafios do profissional de relações públicas - Lobo, Cecília Moreira [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The enterprises are in the midst of a competitive and open market, in which, rapidly, new enterprises are created, international competitors are installed on the local market and products and services are invented or improved to ensure quality, sophistication and low cost. In this scenario, the familial enterprises seek survival through new information and strategies to solve existing conflicts and overcome the challenges of the globalized market. However, resistance to change is a factor common to more traditional familial enterprise culture, therefore, modify solid structures, built over many years, reflects insecurity, fragility and threats facing the different. This project aims to analyze the brazilian familial enterprise, in particular the enterprise Móveis Zacarias, as its historical trajectory, representativeness, economic importance, concept, structure, culture and problems that are peculiar, for example, problems with succession, management, professionalism and communication. In addition to demonstrating the importance of Public Relations professional in mediating conflicts in family businesses. In addition to demonstrating the importance of PR, that when using any of the communication tools, can mediate and facilitate the relationship between members of the family business, and maintain both systems, leading to cooperation between business and family through preventive actions

As empresas encontram-se em meio a um mercado competitivo e aberto, em que, aceleradamente, novas empresas são criadas, concorrentes internacionais instalam-se no mercado local e produtos e serviços são inventados ou aprimorados para garantir qualidade, sofisticação e baixo custo. Diante deste cenário, as empresas familiares buscam sua sobrevivência, através de novas informações e estratégias capazes de sanar os conflitos existentes e superar os desafios do mercado globalizado. Porém, a resistência às mudanças é fator comum à cultura empresarial familiar mais tradicional, pois modificar estruturas sólidas, construídas ao longo de muitos anos, reflete insegurança, fragilidade e ameaças diante do diferente. Este projeto tem como objetivo analisar a empresa familiar brasileira, em especial, a empresa Móveis Zacarias, quanto a sua trajetória histórica, representatividade, importância econômica, conceito, estrutura, cultura e problemas que lhe são peculiares, como por exemplo, problemas com a sucessão, gestão, profissionalização e comunicação. Além de demonstrar a importância do profissional de Relações Públicas, que ao utilizar-se das ferramentas de comunicação, pode mediar e facilitar o relacionamento entre os membros da empresa familiar, e conservar ambos os sistemas, levando à cooperação entre empresa e família por meio de ações preventivas
Keywords: Empresas familiares; Relações publicas; Comunicação; Family-owned business enterprises